A bioplex analysis of cytokines and chemokines in first trimester maternal plasma to screen for predictors of miscarriage. - Natalie J Hannan; Katerina Bambang; Tu'uhevaha J Kaitu'u-Lino; Justin C Konje; Stephen Tong (PLoS ONE)
Background We have previously shown in two independent cohorts that circulating first trimester Macrophage Inhibitory Cytokine-1 (MIC-1) levels are lower in women in early pregnancy who are destined to miscarriage. While promising, the diagnostic performance of measuring MIC-1 alone was not sufficient for it to be a useful predictive test for miscarriage. Besides MIC-1, there are other cytokines, as well as chemokines, involved in facilitating early pregnancy. We reasoned that screening these factors in maternal plasma could uncover other predictive markers of miscarriage. Methods This was a nested case control study, of 78 women from a prospective study of 462 attending the Early Pregnancy Assessment Unit in the first trimester (EPAU) with a threatened miscarriage; 34 of these subsequently miscarried (cases) and 44 went on to have a normal delivery (controls) Cytokines IL-1β, IL-6 and IL-10, and the chemokines, CXCL8, CCL2, CCL5, CCL7 and CX3CL1 were measured in plasma from our cohort. Results The cytokines IL-1β, IL-6, IL-10 and the chemokine CXCL8 were not detectable in first trimester plasma. The chemokines CCL2, CCL5, CCL7 and CX3CL1 were detectable in all samples but levels did not vary across 5-12 weeks of gestation among controls. Plasma levels of these chemokines were no different in the miscarriage cohort compared to controls. Conclusion The chemokines CCL2, CCL5, CCL7 and CX3CL1 were detectable in plasma during the first trimester while IL-1β, IL-6, IL-10 and CXCL8 were not. However, none of the cytokines and chemokines screened were different in maternal plasma in cases or controls. These therefore do not appear to have potential for application as predictive biomarkers of miscarriage.